2022
DOI: 10.1111/ijfs.15594
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endogenous protease activity and protection of histomorphical integrity during refrigerated storage of grass carp fillets by treatment with natural edible di‐ and tri‐carboxylic acids

Abstract: Summary In this study, by dipping grass carp fillets with 10 mM di‐ and tri‐carboxylic acid solutions individually before storage at 4 °C for 10 days, the application potential of these acids in mitigating softening of fish was investigated through analysing shear force, pH, endogenous cathepsin activities, myofibrillar proteolysis and histomorphological characteristics. The results suggested that maleic acid, fumaric acid and tartaric acid were significantly effective against softening of grass carp muscle, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…6 showed that the activities of cathepsin B, D, H, L, calpain and serine protease were significantly correlated with TCA-soluble peptides. Consistently, previous study used di- and tri-carboxylic acids caused cathepsins activity reduction by 20 %–90 % and then reduced the protein degradation rate ( Ge et al, 2022 ). Therefore, the decrease of protein degradation rate might be caused by the UHP treatment decreased the activities of endogenous protease.…”
Section: Discussionsupporting
confidence: 85%
“…6 showed that the activities of cathepsin B, D, H, L, calpain and serine protease were significantly correlated with TCA-soluble peptides. Consistently, previous study used di- and tri-carboxylic acids caused cathepsins activity reduction by 20 %–90 % and then reduced the protein degradation rate ( Ge et al, 2022 ). Therefore, the decrease of protein degradation rate might be caused by the UHP treatment decreased the activities of endogenous protease.…”
Section: Discussionsupporting
confidence: 85%